EDUKASI PERILAKU CERDIK PADA LANSIA DENGAN HIPERTENSI DI WILAYAH KERJA PUSKESMAS BANJAR 1 - Maharani, Indy Zafira; Yuniarti, Mellynia; Sari, Neng Ratna; Aulia, Tri Wahyuni; Farsida, Farsida; Syahniar, Rike (Abdi Masyarakat, 2021)
In general, hypertension is an asymptomatic condition, namely abnormally high pressure in the arteries causing an increased risk of stroke, heart failure, heart attack, and kidney damage which is the leading cause of chronic heart failure. An unhealthy lifestyle and a history of hypertension can trigger hypertension. The community has an essential role in preventing non-communicable diseases such as hypertension and fostering a culture of clean and healthy living behavior (PHBS) in the community. PHBS on the prevention of non-communicable diseases is implemented through the "CERDIK" activity, an acronym for "Regular health checks, Get rid of cigarette smoke, Diligent physical activity, healthy diet with balanced calories, Adequate rest and Manage stress." The purpose of this community service is to provide counseling to the elderly about CERDIK (regular health checks, getting rid of cigarette smoke, diligent physical activity, healthy diet and balanced nutrition, adequate rest, and managing stress). This activity consists of CERDIK Gymnastics, lectures/counseling, and questions and answers. The output of this activity is expected that the elderly can understand hypertension and apply CERDIK behavior.